1992
DOI: 10.1128/mcb.12.8.3346
|View full text |Cite
|
Sign up to set email alerts
|

Can, a putative oncogene associated with myeloid leukemogenesis, may be activated by fusion of its 3' half to different genes: characterization of the set gene.

Abstract: The translocation (6;9)(p23;q34) in acute nonlymphocytic leukemia results in the formation of a highly consistent dek-can fusion gene. Translocation breakpoints invariably occur in single introns of dek and can, which were named icb-6 and icb-9, respectively. In a case of acute undifferentiated leukemia, a breakpoint was detected in icb-9 of can, whereas no breakpoint could be detected in dek. Genomic and cDNA cloning showed that instead of dek, a different gene was fused to can, which was named set. set encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
296
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(302 citation statements)
references
References 37 publications
2
296
0
4
Order By: Relevance
“…These two proteins have different amino termini of 37 amino acids (␣) and 24 amino acids (␤) but are otherwise identical throughout the other 253 amino acids of their sequences (43). Interestingly, the SET protein is a member of a chimeric fusion protein, SET-CAN, that arises as a result of chromosome translocations in acute undifferentiated leukemia (45). A nearly full-length SET protein is present in the SET-CAN fusion with only the last seven amino acids of SET lost upon translocation.…”
Section: Resultsmentioning
confidence: 99%
“…These two proteins have different amino termini of 37 amino acids (␣) and 24 amino acids (␤) but are otherwise identical throughout the other 253 amino acids of their sequences (43). Interestingly, the SET protein is a member of a chimeric fusion protein, SET-CAN, that arises as a result of chromosome translocations in acute undifferentiated leukemia (45). A nearly full-length SET protein is present in the SET-CAN fusion with only the last seven amino acids of SET lost upon translocation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that nucleosome assembly protein-I (NAP-I) has significant amino acid sequence similarity to TAF-I, and that it can substitute for TAF-I activity in the replication of Ad core DNA (von Lindern et al 1992a;Nagata et al 1995). Nucleosome assembly protein (NAP-I), which contains three negatively charged regions, is found in various eukaryotic cells and has been shown to interact with cellular histones and to facilitate nucleosome formation (Fujii-Nakata et al 1992;Ishimi et al 1987).…”
Section: Substitution For Taf-i By Nap-imentioning
confidence: 99%
“…TAF-Ib corresponds to the protein encoded by the set gene. The set-can fusion gene derived from chromosomal translocation is thought to be a putative oncogene associated with acute undifferentiated leukaemia (von Lindern et al 1992a). The expression of SET/TAF-Ib is ubiquitous in a variety of cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the association with cyclin-cdks, p21 Cip1 also interacts with a growing number of proteins, indicating that it is involved in the regulation of many other cellular functions (Coqueret, 2003). We have previously reported that p21 Cip1 interacts with the SET protein, which was firstly identified as a CAN-fusion gene in an acute undifferentiated leukemia (von Lindern et al, 1992;Adachi et al, 1994). SET belongs to a family of proteins, which includes the yeast nucleosome assembly protein NAP-I (Kawase et al, 1996), MB20 (Shen et al, 2001), Cell Division Antigen-1 (Chai et al, 2001), nucleolar transforming growth factor-b1 target (Ozbun et al, 2001), supressor of presenilin-2 (Wen et al, 2000) and testis-specific protein Y-encoded (Vogel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%